Figure-Disembedding Is Inferior in Non-autistic Compared to Autistic Individuals but Can Be Improved by Training - Falter-Wagner, Christine M.; Bloch, Carola; Robles, Marta; Horch, Lea; Vogeley, Kai; Georgescu, Alexandra Livia (Frontiers in Psychology, 2022)
Background: Figure-disembedding is one of the most discussed visuo-cognitive functions, in which individuals with Autism Spectrum Disorder (ASD) have been reported to outperform non-autistic individuals. A local processing bias has been assumed to underlie such superior performance patterns. The aim of the current study is to investigate whether processing preferences can be modified by procedural priming. Method: The current study used a procedural priming task (Navon figures) to induce more local or global processing in 25 autistic and 21 typically-developing (TD) control participants, using hierarchical figures preceding the figure-disembedding task. Results: Participants with ASD outperformed non-autistic individuals in the unprimed baseline task version. Their performance was not modulated by priming in either direction (towards a local or global processing style). However, the performance of TD control participants was improved by local priming to the same level as that observed in the ASD group. Conclusions: Figure-disembedding performance in ASD is superior to that in TD control participants and robust against procedural priming. A local processing style seems to pose an advantage to figure-disembedding.